High fertilizer prices contribute to rising global food security concerns - Hebebrand, Charlotte; Laborde Debucquet, David (International Food Policy Research Institute, 2023)
Like people, plants need a multitude of nutrients to thrive. These are categorized into micronutrients, such as zinc and iron; secondary macronutrients, such as calcium and magnesium; and three primary macronutrients: nitrogen (N), phosphorus (P), and potassium (K). Mineral fertilizers provide higher and more plant-accessible nutrients, while organic minerals importantly also provide carbon, which contributes to healthy soils. While efforts to reduce nutrient losses to the environment must be continued and stepped up, it bears emphasizing that fertilizers play a crucial role in agricultural productivity. World market prices for both food and fertilizer (here we focus only on N, P, and K) increased significantly over the past year and a half and have climbed to even higher levels following Russia’s invasion of Ukraine in February, hitting their highest levels yet in March (see Figure 1, +125% from January 2021 to January 2022, +17% from January 2022 to March 2022). While there is an immediate concern about the impact of high food prices on food security, especially in low and middle-income countries, fertilizer price spikes and concerns about availability cast a shadow on future harvests, and thus risk keeping food prices high for a longer period. In this blog post — which draws on data from the new IFPRI fertilizer dashboard; IFASTAT, compiled by the International Fertilizer Association (IFA); and FAOSTAT — we discuss the underlying drivers of current high pric es, explain why the global fertilizer market is particularly susceptible to shocks, and examine which countries are most vulnerable to fertilizer market disruptions. A subsequent post will explore short- and medium-term solutions to address the serious affordability and availability concerns.